Company Strategy Parcel Industry Faces Recovery Post Covid-19 : Stability Strategy Implementation in Effort Maintain Superiority Compete in Parcel Industry - Tanty Sondari; Ahmad Johan (International Journal of Economics and Management Research, 2025)
The industrial sector plays a crucial role as the primary driver and pillar of the national economy as a whole, contributing to increased production, fixed investment, employment, capacity utilization, and exports, even amid the disruptions and challenges caused by the post-COVID-19 pandemic. The current post-COVID-19 recovery period has had a significant impact on Indonesia's economy, ranging from changes in supply chains to shortages of raw materials. Even if raw materials are available, this leads to higher supply costs. This crisis has had a major impact on consumer purchasing power and social inequality. Consumer purchasing power has declined for the first time in a generation, and income loss has been disproportionate among different social groups, leading to a dramatic increase in inequality. External factors like COVID-19 have influenced consumers' willingness to control themselves by changing their shopping behavior. One of the changes that has occurred post-pandemic is a shift in consumer shopping behavior. Therefore, it is essential for companies to implement strategies. One strategy chosen during this recovery period is a stability strategy to maintain competitive advantage amid an uncertain economic climate. The research method applied is a qualitative method to obtain an initial overview of the stability strategies implemented by companies in their efforts to maintain competitive advantage. This research was conducted using a descriptive analysis method. Descriptive analysis is a research method used to describe an object of study using the object of study as a sample and providing conclusions that apply generally without making comparisons or relationships between the variables being studied